Educational tourism and experiential learning: students' perceptions of field trips. Issue 1 (30th June 2020) - Arcodia, Charles; Abreu Novais, Margarida; Cavlek, Nevenka; Humpe, Andreas
Abstract : Purpose: This paper aims to investigate participants' motivations and perceptions of a field trip. Specifically, this paper examines if and how students' perceptions change with time and it explores the main factors for ensuring success in an experiential learning tourism program. Design/methodology/approach: The study gathered and compared data collected in two points in time – immediately at the end of the experience and two months afterward. T -tests for paired samples were used to examine potential differences in perceptions and principal component analysis was used to identify the key factors determining the success of the experience. Findings: The findings indicate that there are various motivations behind participation and that time barely affects perceptions of the experience. Furthermore, three factors emerged as important for meeting expectations, namely, social and professional connections, learning and traditional yet engaging teaching. Research limitations/implications: While the outcomes are useful, they need to be thoughtfully applied because of the small data set. It is important to repeat similar investigations to allow more certainty in the propositions formulated. Furthermore, future studies should evaluate a broader variety of outcomes to determine whether perceptions remain constant. The implications are that educators and destination managers can easily apply these conclusions for the benefit and the findings can inform other field trips and broader experiential initiatives. Originality/value: Despite research on learning outcomes and perceptions of experiential learning having expanded considerably, a fundamental question that remains unanswered is how perceptions of such experiences change and, consequently, when the most appropriate time is to assess participant perceptions. Abstract : 研学旅游与体验式学习：学生对田野实践的认知 摘要 研究目的: 本文的研究目的是为了探讨学生对于研学旅游中田野实践的参与动机和观念。特别地, 本文检验了学生的观念是否以及如何随时间变化, 并探讨了影响体验式研学旅行项目成功实施的关键因素。 研究设计/研究架构/研究方法: 该研究在两个时间点收集数据, 一是在完成体验式学习之后立即进行数据收集, 二是在两个月后再次进行数据收集。研究主要采用配对样本T检验来检验认知的潜在差异, 采用主成分分析法来识别影响该体验能否成功的关键因素。 研究结论: 研究结果表明, 参加体验式研学旅行的人们有着不同的动机, 时间基本不影响参与者对研学体验的认知。此外, 三个因素显得十分重要：社交和专业联系、学习、传统的参与式教学。 研究局限/研究启示: 尽管本研究的结果有重要的实践价值, 但由于样本量相对较小, 需要谨慎应用此研究结果。本研究认为, 有必要在未来的研究中进行类似的重复研究, 以确保所得出的结论具有稳健性。此外, 未来的研究应当考虑更多的结果, 从而判断参与者的认知是否稳定。本文的研究意义有三：教育工作者以及旅游目的地经理人可以轻松应用这些结论来盈利, 可以启发其他类型的田野实践, 启发更一般的体验式学习项目。 原创性/研究贡献: 近来, 虽然关于体验式学习成效、体验式学习认知的研究迅速增加, 但一个尚未被解答的根本性问题是：体验式学习的认知是如何变化的, 因此, 在哪个时间点去评估参与者的认知是最合适的？ Abstract : Turismo educativo y aprendizaje experimental: percepciones de los estudiantes sobre las excursiones Propósito: El propósito de este estudio es investigar las motivaciones y percepciones de un viaje de campo. Específicamente, en este articulo se examina si las percepciones de los estudiantes cambian con el tiempo y se determinan los principales factores para asegurar el éxito de un programa de aprendizaje experimental de turismo. Diseño/metodología/enfoque: El estudio reunió y comparó datos recopilados en dos puntos en el tiempo – directamente después de la experiencia y dos meses después. Se aplico la prueba " t " para muestras emparejadas para examinar las posibles diferencias en las percepciones y se utilizó el análisis de componentes principales para identificar los factores clave que determinan el éxito de la experiencia. Resultados: los resultados indican que hay varias motivaciones detrás de la participación y que el tiempo prácticamente no afecta las percepciones de la experiencia. Además, tres factores surgieron como fundamentales para cumplir con las expectativas de los estudiantes: conexiones sociales y profesionales, aprendizaje y enseñanza tradicional pero dinámica. Limitaciones/implicaciones de la investigación: Si bien los resultados son útiles, deben aplicarse cuidadosamente debido al pequeño conjunto de datos. Es importante repetir investigaciones similares para permitir mayor certeza en las proposiciones formuladas. Además, los estudios futuros deberían evaluar una variedad más amplia de resultados para determinar si las percepciones permanecen constantes. Las implicaciones son que los educadores y los gerentes de destino pueden aplicar fácilmente estas conclusiones para beneficio y los hallazgos pueden informar otras excursiones e iniciativas experimentales más amplias. Originalidad/valor: Si bien la investigación sobre percepciones del aprendizaje experimental se ha ampliado considerablemente, una pregunta fundamental que queda sin respuesta es cómo cambian las percepciones de tales experiencias y, en consecuencia, cuándo es el momento más apropiado para evaluar las percepciones de los participantes.